2021
DOI: 10.1111/jpr.12338
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison of Factors Related to Long Work Hours1

Abstract: This study aimed to examine psychosocial factors related to working long hours, which causes depression, anxiety, and so forth, including karoshi [work to death]. In particular, the issue of working very long hours and its impacts on employees is seen as an urgent issue in Japan, and by clarifying the factors associated with this phenomenon, we aim to contribute to efforts to identify appropriate mitigation measures. We proposed a model of factors related to long work hours from multiple perspectives, and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, participants reported difficulties implementing their self-care strategies in their workplace, often related to Japanese work culture. This accords to a recent study that identified that Japanese employees’ long working hours were associated with the organizational factors such as team norms and leadership [ 51 ], indicating that an organization’s or manager’s understanding of self-care needs to be established for each healthcare worker to care for themselves. While the national policies to stop long working hours have been implemented (e.g., Karoushi Prevention in 2014, Work Style Reform in 2020), traditional cultural value still favors long working: long overtime hours were positively associated with work vigor among Japanese male workers [ 52 ].…”
Section: Discussionsupporting
confidence: 78%
“…However, participants reported difficulties implementing their self-care strategies in their workplace, often related to Japanese work culture. This accords to a recent study that identified that Japanese employees’ long working hours were associated with the organizational factors such as team norms and leadership [ 51 ], indicating that an organization’s or manager’s understanding of self-care needs to be established for each healthcare worker to care for themselves. While the national policies to stop long working hours have been implemented (e.g., Karoushi Prevention in 2014, Work Style Reform in 2020), traditional cultural value still favors long working: long overtime hours were positively associated with work vigor among Japanese male workers [ 52 ].…”
Section: Discussionsupporting
confidence: 78%
“…In fact, Japanese employees consider work as a duty rather than a personal choice and are often confronted with the social expectation to adapt to one's work environment (Sekiguchi, 2006). Furthermore, collectivism encourages practices such as staying at work to help colleagues, even if one has completed their own tasks (Kanai et al, 2022).…”
Section: The Dark Side Of Collectivismmentioning
confidence: 99%
“…Japan has one of the highest number of working hours among developed countries (Yamauchi et al, 2017), which is associated with unfavorable outcomes, such as subjective unhealthiness (Akutsu et al, 2022) and job burnout (Cheung et al, 2018). Extreme examples include Karoshi (death due to overwork) and Karo-Jisatsu, or suicide due to overwork (Kanai et al, 2021); other examples include work-life balance distortion and workaholism (Kanai, 2009). Workaholic, this controversial term, first came into existence by Oates (1968).…”
Section: Introductionmentioning
confidence: 99%
“…, 2018). Extreme examples include Karoshi (death due to overwork) and Karo-Jisatsu, or suicide due to overwork (Kanai et al. , 2021); other examples include work-life balance distortion and workaholism (Kanai, 2009).…”
Section: Introductionmentioning
confidence: 99%